Peran Normatif Ahli Forensik dalam Proses Penyelesaian Perkara Pidana - Hermanto, Intan Putri; , Kuswardhani, S.H,. M.Hum (2017)
This study aims to determine the extent to which the role of forensic experts in solving criminal cases, the help and the position of forensic experts in solving criminal cases, in this study using a form of juridical-normative, because research examines the normative role of forensic experts in solving criminal cases, which in studies using secondary data sources in the form of legislation and court decisions. This study uses a court decision No. 2554 K / Pid.Sus / 2011, the court ruling No. 109 PK / Pid / 2007 and the decision No. 178 / Pid.Sus-ITE / 2015 / PT.BDG. Results of research on the setting and type of forensic experts could be seen in the Criminal Procedure Code, the State Gazette No. 350 of 1937, Police Chief Regulation of the Republic of Indonesia Number 10 of 2009 and the Regulation No. 12 of 2011 on medical police.